Near fields of gasper jet flows with wedged nozzle in aircraft cabin environment. (15th November 2017) - Tang, Zhanqi; Cui, Xujia; Guo, Yong; Jiang, Nan; Dai, Shen; Liu, Junjie
Abstract: The geometry of the outlet nozzle has a direct effect on the near fields of turbulent jets. An attempt is made to modify the gasper jet nozzle by adding wedges of different sizes. The near fields of the wedged gasper jets are measured by a hot-wire anemometer. For the with-wedges cases, the mean velocity exhibits a more rapid decay in the axial direction, and the turbulent intensity is attenuated after the "second potential core." The higher-order statistics, such as skewness and kurtosis, indicate no obvious difference in the downstream region. As the turbulent structures are formed, the energy spectra indicate that their average energy increases under the wedges' perturbation. Then, the anti-axial-symmetry of the transition flows is observed in two characteristic planes. The mean velocity does not exhibit a significant difference between the two planes, but the turbulent intensity in the perturbed plane embodies the wedges' influence. The wedged nozzle affects the energy intensity and diffusion angle of the turbulent structures in the perturbed plane, and the difference from the unperturbed plane is confirmed by the discrepancy spectra. Furthermore, the anti-axial-symmetry is characterized by turbulent intermittency and entrainment. The turbulent intermittency in the perturbed plane performs with a lower value in the near-nozzle region, and evolves into axial-symmetry in the further downstream region. For turbulent entrainment, the entrainment ratio manifests that wedged nozzle reduces the flow mass in the entrainment of ambient air in the downstream region. Highlights: The decay ratio of mean velocity is increased under the impact of wedges. Nozzle wedges modify the turbulent intensity distribution. Non-axial-symmetry are presented in the gasper jet fields. The turbulent intermittency exhibited the lower value. The entrainment is attenuated in the downstream region.